2011
DOI: 10.1016/j.bpj.2011.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Superresolution Imaging of Multiple Fluorescent Proteins with Highly Overlapping Emission Spectra in Living Cells

Abstract: Localization-based superresolution optical imaging is rapidly gaining popularity, yet limited availability of genetically encoded photoactivatable fluorescent probes with distinct emission spectra impedes simultaneous visualization of multiple molecular species in living cells. We introduce PAmKate, a monomeric photoactivatable far-red fluorescent protein, which facilitates simultaneous imaging of three photoactivatable proteins in mammalian cells using fluorescence photoactivation localization microscopy (FPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
160
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(165 citation statements)
references
References 38 publications
2
160
0
3
Order By: Relevance
“…For instance, the emission maxima of MitoTracker Red and ER-Tracker Red differ by 16 nm. They can be distinguished using a ratiometric method by splitting their emission into a shortand a long-wavelength channel; the probe identity can then be determined from the intensity ratio of these two channels (30,32,40).…”
Section: Imaging Mitochondria With Cationic Rosamine and Carbocyaninementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the emission maxima of MitoTracker Red and ER-Tracker Red differ by 16 nm. They can be distinguished using a ratiometric method by splitting their emission into a shortand a long-wavelength channel; the probe identity can then be determined from the intensity ratio of these two channels (30,32,40).…”
Section: Imaging Mitochondria With Cationic Rosamine and Carbocyaninementioning
confidence: 99%
“…It has been further demonstrated that many conventional dyes can be used for super-resolution imaging based on photoswitching/bleaching and localization of single molecules (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Using single-molecule-based super-resolution methods, 3D resolutions down to approximately 10 nm have been demonstrated for fixed samples (21)(22)(23)(24)(25)(26), and live-cell imaging has also been achieved with spatial resolutions of 20-60 nm at time resolutions ranging from 0.5 s to 1 min (27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…In the first application of PALM to living cells, the Hess group showed that influenza hemagglutinin (HA), a protein associated with cholesterolrich membrane domains, resides in irregular clusters on length scales from few nm up to many micrometres; furthermore, these observations discarded the hypothesis that line tension (due to lipid fluid-fluid phase coexistence) is responsible for the shape of the domains [188]. PALM imaging of live fibroblasts has also demonstrated that both transferrin receptor (TfR) and HA are correlated with actin while TfR and HA are uncorrelated, providing with the first direct evidence that TfR and HA live in distinctly different domains and also suggesting a direct interaction of membrane proteins with the actin skeleton [128].…”
Section: Chromosome Organisationmentioning
confidence: 95%
“…PS-CFP2 (converts from cyan to green [137]) and PSmOrange (converts from orange to red [138]) also show good spectroscopic properties and may be used to simultaneously tag two intracellular proteins. PAmKate is the farthest red-shifted photoactivatable protein [128], which facilitated multicolour PALM of cells simultaneously expressing Dendra2, PAmCherry1 and PAmKatetagged proteins with a single excitation wavelength [128].…”
Section: Fluorescent Probes For Localisation Microscopymentioning
confidence: 99%
“…Researchers led by Sam Hess showed 12 that three fluorophores that all emit in the orange-red wavelengths could be distinguished from each other. Conventional microscopy would not be able to separate, say, a greenish-yellow label that emits two green photons for each red one from an orangish-yellow label that emits one green photon for each red one, but super-resolution microscopy can distinguish such signals because emitted photons are attributed to individual proteins.…”
Section: How To Build a Fluorescent Proteinmentioning
confidence: 99%